Size and type of cross-border movements on the border between Spain (Extremadura) and Portugal (Alentejo and the Centro Region) - Gutiérrez Gallego, José Antonio; Pérez Pintor, José Manuel; Mora Aliseda, Julián (Documents d'Anàlisi Geogràfica, 2010)
This study allows us to approach to the socio-economic reality of border spaces shaped by the municipalities of the provinces of Badajoz and Caceres (Spain) and the concelhos and freguesias of the Portuguese districts of Guarda, Castelo Branco, Portalegre, Évora and Beja, to be able to estimate the most characteristic aspects of this landscape and territorial unit. In this respect we must emphasize the importance of the existence of the border in the relations of resident population on its both sides. In this scenario we try to verify how the border influences social relations, mobility, infrastructures, and also how the resident population interacts in these spaces as a result of the influence of the previously mentioned interrelated factors. It allows us to determine the configuration of the border settlements system. Likewise the incidence of different cross-border cooperation actions exercised over these spaces by Spain and Portugal after their entry into the European Union is evaluated.